1981
DOI: 10.1111/j.1398-9995.1981.tb01874.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergens in Cow Hair and Dander

Abstract: Quantitative immunoelectrophoretic methods were used for the analysis of the allergens in cow hair and dander and for comparison with related preparations. The immunoelectrophoretic precipitation pattern of an extract from cow hair and dander showed 17 precipitates. Crossed radioimmunoelectrophoresis showed four of these to be major allergens of the extract, and these allergens are common major allergens in four investigated cow breeds. The allergens are associated predominantly with hair and dander, but they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…SDS-PAGE analysis revealed that all hair extracts showed nearly identical protein patterns and that each had a dominant Bos d 2 band. These results are in accordance with previous studies that have shown only minor interindividual differences in protein patterns [3,24]. In contrast, considerable inter- and within-breed variations were seen in horse and dog allergen extracts [25,26], but no breed-specific allergens were found.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…SDS-PAGE analysis revealed that all hair extracts showed nearly identical protein patterns and that each had a dominant Bos d 2 band. These results are in accordance with previous studies that have shown only minor interindividual differences in protein patterns [3,24]. In contrast, considerable inter- and within-breed variations were seen in horse and dog allergen extracts [25,26], but no breed-specific allergens were found.…”
Section: Discussionsupporting
confidence: 82%
“…milk and beef, or from leather materials. The presence of allergens in such products has been demonstrated by Prahl [3]. In concordance with this observation, milk gave a positive reaction in the present assay (data not shown).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The role of animals in occupational asthma is well recognized. Veterinary surgeons, stockmen and others whose occupation or leisure pursuits require close association with animals may experience allergic reactions including asthma to allergens derived from them, as demonstrated for example from the horse (L0wenstein et al 1976), the cow (Prahl 1981) and the pig (Harries & Cromwell 1982). Recent research interest has focused on the role of experimental animals used in the laboratory in the induction of asthma.…”
mentioning
confidence: 99%